Do women benefit from global production networks? Evidence from the Indonesian footwear industry - Padang Wicaksono; Yulial Hikmah; Rieka Evy Mulyanti (Economies, 2023)
Despite the remarkable improvements in key economic and social standards, the Indonesian footwear industry still struggles to ensure decent work, particularly for women workers. In this paper, female workers are divided into production and non-production workers. Women production workers are used as a proxy for occupational segregation based on sex, called non-skilled workers, while women non-production workers are used as a proxy for women's share of work in managerial and administrative work, called skilled workers. This paper examines the close links between decent work (DW) and global production networks (GPNs) in the Indonesian footwear industry. More specifically, this article scrutinizes fair employment treatment for local female employees within the DW framework in the country's footwear industry with the expansion of GPNs based on Indonesian footwear firm-level panel data from 2001 to 2015. Vertical specialization is a proxy for GPNs and is the main independent variable in this paper. The results show that vertical specialization is in line with the fair treatment indicators and has a significant level for female production workers. In addition, the other independent variable, namely the wages of production workers, has a significant level, and the results are inversely proportional to the fair treatment indicator, while the wages of non-production workers show results that are inversely proportional to female production workers but positive for female non-production workers. This shows that an increase in the wages of production workers is less profitable for female production workers than for female non-production workers. Thus, the results show that the expansion of GPNs in the Indonesian footwear sector has essentially led to improved fair employment treatment, especially for women workers.
Keywords: 330; fair employment treatment; decent work; women workers; global production net-works; footwear industry